PENGARUH KUALITAS LAYANAN SIRKULASI PEMUSTAKA MELALUI INDEKS KEPUASAN MAHASISWA DI PERPUSTAKAAN POLTEKKES KEMESKES PONTIANAK - Martina, Melinia; Hanum, Atiqa Nur Latifa; Saman, Sisilya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research aims to determine the level of user satisfaction and circulation services, as well as the influence of user satisfaction on circulation services at the Pontianak Ministry of Health Polytechnic library. This quantitative study uses a descriptive approach, with a population of all enrolled students from 2019 to 2022, totaling 568 individuals. Using the Slovin formula, the sample size was determined to be 85 respondents. Data was collected through observation and questionnaires, utilizing a Likert scale for measurement. Validity was assessed with a sample size of 30 using the Pearson method, while reliability was tested with a sample of 30 using Cronbach's Alpha. Data analysis included calculating averages and overall means. Hypothesis testing was conducted through simple linear regression and product-moment correlation tests. The results indicate that circulation services scored 4.12, and user satisfaction scored 4.07, both falling in the high assessment range (3.40-4.20). User satisfaction positively and significantly affects circulation services at the library.